Properties of C/C–ZrC composites prepared by precursor infiltration and pyrolysis with a meltable precursor. (19th June 2019) - Li, Yong; Meng, Xiaojun; Jia, Yan; Chen, Si'an; Mei, Min; Li, Guangde
Abstract: A melted ZrC precursor was used to prepare C/C–ZrC composites by precursor infiltration and pyrolysis (PIP) for reducing preparation time and rapid densification. The heat treatment time during the process was optimized. When the C/C–ZrC composites were annealed at 1650 °C after the fourth, eighth, and twelfth cycles, the composites were relatively compact with a few pores, and the density was 2.06 g cm −3 with an open porosity of 19.4%. The composites showed typical non-brittle fractures with numerous carbon fibers and bundle pullouts on the fracture surface. The preparation period was reduced to 12 cycles by using the melted ZrC precursor and the as-prepared composites had an enhanced mechanical properties. The flexural strength of the composites was 149 MPa, and the fracture toughness was 8.68 MPa·m 1/2 . The composites exhibited good ablation resistance, and the linear recession rate was 0.015 mm s −1 during oxyacetylene ablation tests for 60 s.